"Ultra High Dilution 1994" revisited 2015 – the state of follow-up research. Issue 4 (October 2015) - Endler, P. Christian; Schulte, Jurgen; Stock-Schroeer, Beate; Stephen, Saundra
Abstract : Background: The "Ultra High Dilution 1994" project was an endeavour to take stock of the findings and theories on homeopathic extreme dilutions that were under research at the time in areas of biology, biophysics, physics and medicine. The project finally materialized into an anthology assembling contributions of leading scientists in the field. Over the following two decades, it became widely quoted within the homeopathic community and also known in other research communities. The aim of the present project was to re-visit and review the 1994 studies from the perspective of 2015. Method: The original authors from 1994 or close laboratory colleagues were asked to contribute papers covering their research efforts and learnings in the period from 1994 up to 2015. These contributions were edited and cross-referenced, and a selection of further contributions was added. Results: About a dozen contributions reported on follow-up experiments and studies, including further developments in theory. Only few of the models that had seemed promising in 1994 had not been followed up later. Most models presented in the original publication had meanwhile been submitted to intra-laboratory, multicentre or independent scrutiny. The results of the follow-up research seemed to have rewarded the efforts. Furthermore, contributions were provided on new models that had been inspired by the original ones or that may be candidates for further in-depth ultra high dilution (UHD) research. Conclusion: The project "Ultra High Dilution 1994 revisited 2015" is the latest output of what might be considered the "buena vista social club" of homeopathy research. However, it presents new developments and results of the older, established experimental models as well as a general survey of the state of UHD research.